Spolna diferenciacija na primeru transformacije novinarskega poklica - Humer, Živa (Teorija in praksa, 2017)
The article discusses the feminisation of journalism in the context of gender inequality in the media. We point out that the proportion of female journalists and editors in recent decades has grown significantly in journalism, despite the characteristics of masculinisation (long and atypical working hours, business trips, inflexibility in the work-life balance). Meanwhile, inequalities in the media on both the employment level and the level of media representation have not been reduced but maintained and reproduced through the existing gendered organisational structures and processes, management and decision-making positions. Based on analysis of 10 interviews with the management of three TV stations (TV Slovenia, POP TV and Planet TV), we find that journalism's transformation from the gender perspective is recognised solely as a quantitative indicator of the increasing number of women in journalism and, consequently, as gender equality having been achieved in employment in television stations. We note that the failure to address critical issues related to gender and gender equality in management and employment in the media enables the reproduction of the existing gender inequality in the media.
Keywords: Feminizacija; Feminization; Journalism; Mass media; Množični mediji; Novinarstvo; Sex differentiation; Slovenia; Slovenija; Spolna diferenciacija; Television; Televizija